Speaking Skills Attitude Scale for Primary School Students: Validity and Reliability Study - Emel Guvey Aktay; Ferah Mermi (Universitas Pendidikan Indonesia, 2022)
The current study was conducted to develop a scale to measure students’ speaking skills attitudes. This study is a scale of development study. The current research study group comprises 225 third and fourth-grade students attending primary schools in Mugla in the 2019-2020 school year. After conducting a literature review and interviews with primary school students, an item pool consisting of 106 items was created. KMO value was found to be .759. The exploratory factor analysis was conducted on the 32-item scale, and a scale composed of 18 items gathered under three sub-dimensions was obtained. Cronbach Alpha test was found to be .78. Thus, it can be said that the scale developed to measure primary school students’ attitudes towards speaking skills is a reliable and valid scale. In addition, it can be noted that this scale will provide convenience in measuring primary school students’ attitudes towards speaking skills and in evaluating and interpreting students’ attitudes.